Akibat Hukum dalam Penyelesaian Sengketa Akad Murabahah: Analisis Klausul Pilihan Forum di Pengadilan Negeri - Bambang Widagdo Suryaning Projo; Siti Hamidah; Nur Chanifah (CV. AFDIFAL MAJU BERKAH, 2024)
The development of Islamic banking in Indonesia, with the Murabahah financing contract dominating, is not free from disputes among the parties involved. Dispute resolution can be settled out of court (non-litigation), one of which can be through the National Sharia Arbitration Board (Basyarnas) and through the Religious Courts (litigation). Legislation has regulated the absolute authority of the institution responsible for litigation dispute resolution through Article 49 letter (i) of Law Number 3 of 2006, as amended in Law Number 50 of 2009 Regarding the Second Amendment of Law Number 7 of 1989 and Article 55 paragraph (1) of Law Number 21 of 2008 Regarding Islamic Banking, namely the Religious Court. A conflict of norms appears in the Murabahah financing contract, which still includes a clause for dispute resolution litigation in the District Court. This raises the first issue formulation regarding what the legal consequences are for the parties in the Murabahah financing contract with the choice of forum clause in the District Court when resolving litigation disputes and what choice of forum clause is stipulated in the Murabahah financing contract to provide a balanced position for the parties when resolving litigation disputes.